IMPLEMENTASI MULTIMODEL GROUP INVESTIGATION DAN MURDER (MGIM) PADA PEMBELAJARAN MATERI LARUTAN PENYANGGA - Sidik Prasetyo; Syahmani Syahmani (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2011)
t has been conducting research about Implementation of learning multiple model Group Investigation and MURDER in learning chemistry especially Buffer Solution. This study aims at finding out the effetiveness of the learning multiple model Group Investigation and MURDER (MGIM) could significantly improve students. This quasi-experimental study involved students of class XI SMAN 3 Banjarmasin of South Kalimantan as a subject. Test instruments were used for measuring students learning outcome. Questionnaire were used for measuring students affective aspect. Students activity measured by observer. By using one way Anava and LSD analysis, this study shows that  the implementation of MGIM in Buffer Solution gives better activity learning outcome than just GI and conventional learning. Implementation of MGIM in Buffer Solution gives better learning activity and affective learning outcome too.Key words: multiple model, GI, MURDER, and Buffer Solution